If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(5X + -3) = 46X Reorder the terms: 9(-3 + 5X) = 46X (-3 * 9 + 5X * 9) = 46X (-27 + 45X) = 46X Solving -27 + 45X = 46X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-46X' to each side of the equation. -27 + 45X + -46X = 46X + -46X Combine like terms: 45X + -46X = -1X -27 + -1X = 46X + -46X Combine like terms: 46X + -46X = 0 -27 + -1X = 0 Add '27' to each side of the equation. -27 + 27 + -1X = 0 + 27 Combine like terms: -27 + 27 = 0 0 + -1X = 0 + 27 -1X = 0 + 27 Combine like terms: 0 + 27 = 27 -1X = 27 Divide each side by '-1'. X = -27 Simplifying X = -27
| (n-2)180=1980 | | 11.97+v=5v-.11 | | (n-2)180=1989 | | y^2=2*x+1 | | 28x-28=28 | | n-2(180)=1980 | | x^2+10x-121=0 | | (10x+5)=(8x+25) | | 60x^2-120=0 | | 83-6x=9x+10x | | 4x=110-6x | | 3x+2/3+4x-5/4-3x-8/8=16 | | -152+7x=180 | | 6+V=7+V | | 4x^2+8x=-10 | | 13.91+.09h=14.14-.08h | | 5/8+n=3 | | 13-3x+2+6x-2x-2x-1=21 | | 6/3-n=1 | | (90-5x)+(62-2x)=180 | | 6n-3=1 | | 5x-9=6x+6 | | 4/n+9=12 | | n*3+9=-6 | | -25=x+1 | | -(a/b)=(-a)/b | | n/3-5 | | 2/x=5/x+6 | | x^3-6x^2+9x=x | | 4x^2-30x+45=11 | | 13.93+.09h=14.14-.08h | | 13.84+.09h=14.14-.08h |